7. IMPACT OF CHROMOSOMAL MOSAICISM IN IVF OUTCOMES: EXPERIENCE FROM TWO HUNDRED MOSAIC EMBRYOS TRANSFERRED PROSPECTIVELY. (August 2019) - Spinella, F.; Biricik, A.; Minasi, M.G.; Varrichhio, M.T.; Corti, L.; Viganò, P.; Baldi, M.; Surdo, M.; Cotroneo, E.; Fiorentino, F.; Greco, E.
Abstract : Introduction: Chromosomal mosaic embryos are characterized by the presence of chromosomally different cell lines within the same embryo. In a recent published study, we have demonstrated that mosaic embryos hold the potential to implant and result in the birth of healthy babies. Therefore, the transfer of these embryos is now offered as an option for women who undergo in vitro fertilization (IVF) resulting in only mosaic embryos but no euploid embryos for transfer. However, there is still few data concerning the impact of mosaicism on viability, and the classification of such embryos in relation with their reproductive potential is unclear. Here we investigated if chromosomal constitution of mosaic embryos influences the clinical outcome of in vitro fertilization treatments Material and methods: The transfer of mosaic embryos was offered to 200 women for whom IVF had resulted in no euploid embryos between May 2016-May 2018. Trophectoderm (TE) biopsy was performed on Day-5 of development or Day6/7 for slow growing embryos. The clinical outcome obtained after transfer of mosaic embryos with different chromosomal constitution was compared with each other and with that obtained from a control group of 500 euploid blastocysts. Comprehensive chromosome testing PGT-A was performed using high resolution next generation sequencing (NGS) methodology. TE biopsies were classified as mosaic if they had 20%-80% abnormal cells. For statistical analysis mosaic embryos were divided in four groups based on chromosomal constitution: mosaic monosomy (single and double monosomies; MM), mosaic trisomy (single and double trisomies, MT), mosaic complex aneuploidy (more than two different aneuploidies; MC) and mosaic segmental aneuploidy (single and double deletion or insertion >5Mb, MS). Results: MM showed significant higher birth rate compared to MT (46% vs 24%, p=0.02), MC (46% vs 23%, p=0.03) and MS (46% vs 22%, p=0.02). No significant difference was observed in clinical outcome between the groups MT, MC and MS. A comparison of the clinical outcomes with control euploid group showed no significant difference between euploid control and MM, while a significant low implantation rate (55.4% vs 37% MT, vs 31% MC, vs 23% MS, p<0.05) and live birth rate (48.4% vs 24% MT, 23% MC, vs 22% MS, p<0.05) between the euploid control and rest of mosaic groups was observed (Table). The highest biochemical pregnancy rate (31%) and early abortion rate (13%) was observed in MS, and MT, respectively. Conclusion: The study demonstrated that embryos with MT, MS and MC aneuploidies have lower chances of resulting with birth of healthy babies compared to embryos with MM. More interestingly, no difference has been find in clinical results between MM and euploid control group. These findings should be considered for genetic counseling.